CLASSIFICATION OF FINISHED PRODUCTS OF FRUIT AND BERRY ENTERPRISES FOR ACCOUNTING AND CONTROL NEEDS - ZABRODSKYI, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of the problem of classification of finished products of fruit and berry processing enterprises for accounting and control purposes. The relevance of the topic is due to the fact that modern enterprises in this industry produce a wide range of products, which complicates the processes of accounting, quality control and inventory management. The lack of a clear and systematic classification leads to a number of problems, including: complexity of accounting, violation of quality control, complication of inventory management, difficulties in production planning and complication of marketing research. The purpose of the article is to optimize the classification system for finished products of fruit and berry processing enterprises for accounting and control purposes in order to increase the efficiency of production management and product sales. The main material of the article is devoted to the justification of the need for classification of finished products for effective management of the enterprise. It is substantiated that the specifics of the activities of fruit and berry processing enterprises, which will influence the construction of product classification, are as follows: high dependence on seasonality, short shelf life of raw materials, high sanitary requirements, a wide range of products, the need to preserve organoleptic properties and high competition in the market. A classification of finished products of fruit and berry processing enterprises is proposed according to the following characteristics: type of raw material, types of products, processing method, degree of readiness, type of packaging, purpose of products, shelf life, seasonality of production and consistency. Special attention is paid to the classification of fruit and berry fillers, which are gaining increasing popularity on the domestic market. A classification of fruit and berry fillers is proposed according to the following characteristics: type of raw material, production technology, consistency, functional purpose and composition. It has been established that effective classification of finished products is the key to the successful functioning of fruit and berry processing enterprises in modern market conditions. It allows optimizing production processes, improving product quality, and ensuring successful competition in the market.